PERAN GURU DALAM MENINGKATKAN KEAKTIFAN SISWA DI KELAS - Herwani, Herwani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
The problems that occur show that students have not been able to be active in learning and the teacher has not been maximized in managing the class. This study aims to describe the teacher's role in managing the classroom to increase student activeness in the classroom. This research is a literature study which literature, with documentary data collection and analysis using content analysis. The results state that the teacher's role in organizing an active class is an effort to organize life in the classroom in order to create an effective and efficient learning process. Teachers use collaborative methods, namely involving students actively in the learning process in it, students are more confident, brave and able to work together in expressing the arguments they get in the learning process, students who are not responsible for the tasks assigned by the teacher, or families who do not cooperate with the teacher. The solution is that teachers must be more creative in using learning methods, students are given advice and motivation, families and schools work together in helping to improve achievement in madrasah.